On the nature of psyche - "Jung, Carl Gustav" (London, 2004)
Jung's discovery of the 'collective unconscious', a psychic inheritance common to all humankind, transformed the understanding of the self and the way we interpret the world. In On the Nature of the Psyche Jung describes this remarkable theory in his own words, and presents a masterly overview of his theories of the unconscious, and its relation to the conscious mind. Also contained in this collection is On Psychic Energy, where Jung defends his interpretation of the libido, a key factor in the breakdown of his relations with Freud. For anyone seeking to understand Jung's insights into the human mind, this volume is essential reading.
Keywords: Psychology